Sabai Nan Aluih: dari Kaba Klasik ke Komik - Lastry Monika (JENTERA: Jurnal Kajian Sastra, 2022)
The discussion in this paper aims to discuss Sabai Nan Aluih which was originally a classic work which was transformed into a new work in the form of a comic. It happened as a reception of a literary form. Both works are analyzed and interpreted by looking at the relationship between works related to the horizon of hope as stated by Hans Robert Jauss. Based on this theory, the presence (those who are present) and the absence (those who are not present) are stated as a form of respect for the two works that are used as object materials. The results of the analysis show that there are a number of presences and absences between the two works. The presence and absence of the two works can be seen based on the plot, setting of the story, and the choice of words used. The number of attendances and absences occurs because or is intended to be adjusted to the different times of the presence of the two works. However, these two things do not change the main idea of the story of Sabai Nan Aluih. AbstrakPembahasan dalam tulisan ini bertujuan untuk membahas Sabai Nan Aluih yang pada awalnya merupakan karya klasik bertranformasi menjadi karya baru berupa komik. Hal itu terjadi sebagai bentuk resepsi sastra. Kedua karya tersebut dianalisis dan ditafsir dengan melihat hubungan antarkarya yang berkaitan dengan horizon harapan sesuai yang dikemukakan oleh Hans Robert Jauss. Berdasarkan teori tersebut dikemukakan presence (yang hadir) dan absence (yang tak hadir) sebagai wujud dari respesi atas kedua karya yang dijadikan sebagai objek material. Adapun hasil analisis menunjukkan bahwa terdapat sejumlah presence dan absence antarkedua karya. Presence dan absence yang terdapat dalam kedua karya dapat dilihat berdasarkan alur, latar cerita, dan pilihan kata yang digunakan. Adanya sejumlah presence dan absence terjadi dikarenakan atau bertujuan untuk disesuaikan dengan perbedaan zaman hadirnya kedua karya tersebut. Akan tetapi, kedua hal itu secara keseluruhan tidak mengubah gagasan utama dari cerita Sabai Nan Aluih.